The effect of motivational interviewing on physical activity level among older adults: a systematic review and meta-analysis. (2nd July 2020) - Akinrolie, Olayinka; Barclay, Ruth; Strachan, Shaelyn; Gupta, Akanksha; Jasper, Unyime S.; Jumbo, Samuel U.; Askin, Nicole; Rabbani, Rasheda; Zarychanski, Ryan; Abou-Setta, Ahmed M.
Abstract: Aim: To determine the reported effect of randomized controlled trials (RCTs) using Motivational Interviewing (MI) to advance physical activity among older adults. Methods: We searched for RCTs in MEDLINE, EMBASE, CINAHL, AgeLine, PsycINFO and Cochrane Library from inception until March, 2019. Identified trials that used MI for improving physical activity in community-dwelling older adults (≥65 years). Results: From 5616 citations identified from the search, we included three trials (four publications). There was no evidence of a significant difference between the effect of MI and usual care on physical activity in older adults (Standard Mean Difference (SMD) -0.02, 95% Confidence Interval (CI) 0.05 to 0.46, I 2 16%; 3 trials; 84 participants). Conclusion: There is insufficient evidence to support the effect of MI on improving physical activity among older adults. There is a need for more high quality trials to show that MI is beneficial in older adults who are physically inactive.